The Margins of Late Medieval London, 1430-1540 - Berry, Charlotte (New Historical Perspectives, 2022)
The Margins of Late Medieval London is a powerful study of medieval London's urban fringe. Seeking to unpack the complexity of urban life in the medieval age, this volume offers a detailed and novel approach to understanding London beyond its institutional structures. Using a combination of experimental digital, quantitative and qualitative methodologies, the volume casts new light on urban life at the level of the neighbourhood and considers the differences in economy, society and sociability which existed in different areas of a vibrant premodern city. It focuses on the dynamism and mobility that shaped city life, integrating the experiences of London's poor and migrant communities and how they found their place within urban life. It describes how people found themselves marginalized in the city, and the strategies they would employ to mitigate that precarious position.